Designing and manufacturing of plastic bricks for construction application - Espiritu, Laurence Kristoffer P.; Padilla, Justin Christian S.
The trend of sustainable energy is growing amongst the field of construction. There have been multiple researches and studies made to further expand and develop these sustainable technologies. These technologies aim to minimize the excess waste and in turn, produce solutions that are beneficial for the environment. This study aims to tackle the issue of growing plastic wastage by introducing a plastic building material that will be used in construction. This plastic building material is made of one hundred percent (100%) plastic, namely, HDPE and PET, and is manufactured with the use of a compression molding machine. The molding machine has four components, the oven, frame, electronics, and hydraulic press. Steel molds are also made with stainless steel, nuts, and bolts, and used in molding the plastics together. The optimal composition of this is found to be made up of 70% HDPE and 30% PET, obtaining an ultimate compressive strength of 30.845 MPa. A prototype is created with the composition mentioned, obtaining a weight of 2.078 kg. These plastic bricks are interlocking meaning it will no longer need an adhesive such as cement therefore lessening the labor and increasing the speed of construction. The total cost for one square meter of the lego brick is Php 2949.48. This shows that there is a feasible, solution in the creation of the brick, and thus provides a possible alternative for the application in construction.